2010
DOI: 10.4142/jvs.2010.11.1.59
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of avian metapneumovirus from chickens in Korea

Abstract: Avian metapneumovirus (aMPV) causes upper respiratory tract infections in chickens and turkeys. Although the swollen head syndrome (SHS) associated with aMPV in chickens has been reported in Korea since 1992, this is the study isolating aMPV from chickens in this country. We examined 780 oropharyngeal swab or nasal turbinate samples collected from 130 chicken flocks to investigate the prevalence of aMPV and to isolate aMPV from chickens from 2004-2008. Twelve aMPV subtype A and 13 subtype B strains were detect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 27 publications
1
26
1
Order By: Relevance
“…Kwon et al reported that two aMPV-As out of the 25 detected aMPV were successfully isolated in Vero cells [29]. Our study had similar results.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Kwon et al reported that two aMPV-As out of the 25 detected aMPV were successfully isolated in Vero cells [29]. Our study had similar results.…”
Section: Discussionsupporting
confidence: 88%
“…The pathogen was serially cultured through 13 passages in Vero cells and then identified by electron microscopy. We observed that the pathogen particle was an enveloped virus characterized by a diameter of 20-500 nm and multiple morphologies ( Figure 3E, F), similar to that of aMPV [14,29]. Vero cells were inoculated with S-01 at an MOI of 0.…”
Section: Novel Virus Is Isolated and Characterized As Ampv-like Virusmentioning
confidence: 88%
“…The pathogen was serially cultured through 13 passages in Vero cells and then identified by electron microscopy. We observed that the pathogen particle was an enveloped virus characterized by a diameter of 20–500 nm and multiple morphologies (Figure 3E, F), similar to that of aMPV [14],[29]. Vero cells were inoculated with S-01 at an MOI of 0.1.…”
Section: Resultsmentioning
confidence: 99%
“…The virion particles in the pellet were visualized by electron microscopy (EM) as described by Kwon et al [29]. …”
Section: Methodsmentioning
confidence: 99%
“…It causes acute rhinotracheitis (TRT) in turkeys and swollen head syndrome (SHS) in chickens, leading to serious financial losses [18][19][20]. Since aMPV was first detected in South Africa in 1978 [21], many countries and regions have reported aMPV-infected poultry [22][23][24][25][26][27][28][29]. Based on the classification of hMPV, aMPV strains have been divided into four subtypes, A, B, C, and D (also designated aMPV/A, aMPV/B, aMPV/C, and aMPV/D) [22,[30][31][32].…”
Section: Introductionmentioning
confidence: 99%